Innovation of knowledge intensive service firms in urban areas - Andrea Hammer (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
This paper investigates the agglomeration of Knowledge Intensive Service (KIS) firms in urban areas. In accordance with the Regional Innovation Systems approach it is argued that cities provide crucial innovation advantages working as centripetal forces for KIS. Applying multivariate logit regressions to a company survey of the city of Karlsruhe, the second largest city of the German federal state of Baden-Württemberg, shows positive effects of local cooperation and urban infrastructures on the innovation probability of KIS firms. However, the effects vary with the type of innovation pursued, thus demonstrating a high complexity of local relations conducive to KIS firm innovation.
urn:nbn:de:swb:90-436889
Keywords: O31; R12; 330; Knowledge Intensive Services; Regional Innovation Systems; urban innovation; innovation in services; local cooperation; urban infrastructure